Annual Plan 1992-93 - Planning Commission (Planning Commission, 1992)
The Indian economy had moved on to a higher growth path in the eighties. During the second half of the eighties covering the Seventh Plan period, the economy grew at an annual average rate of 5.8 percent. Prices rose somewhat moderately during the Seventh Plan. The annual average rate of inflation during the Seventh Plan period was 7 to 8 per cent. Dollar value of exports had grown at an annual average rate of about 12 per cent. However, the balance of payments situation deteriorated slowly and steadily. During the Seventh Plan period, the current account deficit as percentage of GDP averaged 2.4 percent - far above 1.6 per cent projected for this period in the plan document. This deterioration in the balance of payment occurred despite robust growth in exports.
Government of India Planning Commission
Government of India Planning Commission